MicroRNA regulation in an ancient obligate endosymbiosis. Issue 8 (22nd January 2018) - Feng, Honglin; Wang, Lingyu; Wuchty, Stefan; Wilson, Alex C. C.
Abstract: Although many insects are associated with obligate bacterial endosymbionts, the mechanisms by which these host/endosymbiont associations are regulated remain mysterious. While microRNAs (miRNAs) have been recently identified as regulators of host/microbe interactions, including host/pathogen and host/facultative endosymbiont interactions, the role miRNAs may play in mediating host/obligate endosymbiont interactions is virtually unknown. Here, we identified conserved miRNAs that potentially mediate symbiotic interactions between aphids and their obligate endosymbiont, Buchnera aphidicola . Using small RNA sequence data from Myzus persicae and Acyrthosiphon pisum, we annotated 93 M. persicae and 89 A. pisum miRNAs, among which 69 were shared. We found 14 miRNAs that were either highly expressed in aphid bacteriome, the Buchnera ‐housing tissue, or differentially expressed in bacteriome vs. gut, a non‐ Buchnera ‐housing tissue. Strikingly, 10 of these 14 miRNAs have been implicated previously in other host/microbe interaction studies. Investigating the interaction networks of these miRNAs using a custom computational pipeline, we identified 103 miRNA::mRNA interactions shared between M. persicae and A. pisum . Functional annotation of the shared mRNA targets revealed only two over‐represented cluster of orthologous group categories: amino acid transport and metabolism, and signal transduction mechanisms. Our work supports a role for miRNAs in mediating host/symbiont interactions between aphids and their obligate endosymbiont Buchnera . In addition, our results highlight the probable importance of signal transduction mechanisms to host/endosymbiont coevolution.